Experimental realization of linearly polarized x-ray detected ferromagnetic resonance - C Klewe; S Emori; Q Li; M Yang; B A Gray; H-M Jeon; B M Howe; Y Suzuki; Z Q Qiu; P Shafer; E Arenholz (New Journal of Physics, 2022)
We present the first theoretical and experimental evidence of time-resolved dynamic x-ray magnetic linear dichroism (XMLD) measurements of GHz magnetic precessions driven by ferromagnetic resonance in both metallic and insulating thin films. Our findings show a dynamic XMLD in both ferromagnetic Ni _80 Fe _20 and ferrimagnetic Ni _0.65 Zn _0.35 Al _0.8 Fe _1.2 O _4 for different measurement geometries and linear polarizations. A detailed analysis of the observed signals reveals the importance of separating different harmonic components in the dynamic signal in order to identify the XMLD response without the influence of competing contributions. In particular, RF magnetic resonance elicits a large dynamic XMLD response at the fundamental frequency under experimental geometries with oblique x-ray polarization. The geometric range and experimental sensitivity can be improved by isolating the 2 ω Fourier component of the dynamic response. These results illustrate the potential of dynamic XMLD and represent a milestone accomplishment toward the study of GHz spin dynamics in systems beyond ferromagnetic order.